Disfavit: Organic Liquid Food for Neurorehabilitation and Nutritional Fulfillment in Post-Stroke Patients with Dysphagia - Hariantha, Komang Kananta Candra; Asmara, Anak Agung Gde Anom Putra; Savitri, Anak Agung Istri Yuri Pratista (Eduvest - Journal of Universal Studies, 2025)
Dysphagia, or difficulty swallowing and chewing, often occurs as a result of medical conditions such as strokes that damage the cranial nerves. This condition has the potential to cause malnutrition, aspiration, and decreased quality of life, especially in the elderly. Dietary modification is important, but special products for dysphagia patients with complete nutritional content are still limited. To overcome this, DisfaVit comes as a liquid food in the form of a soluble powder that is soft, filling, high in calories, and low in sugar. Made from organic ingredients, DisfaVit uses moringa leaves, banana peels, and white snapper scales—nutrient-rich leftovers from the food industry—with the addition of soy milk powder, soy protein isolate, and guar gum. This study aims to analyze the secondary metabolite content of moringa leaves and banana peels, evaluate the characteristics, quality, and safety of DisfaVit, and identify the most in-demand formulas. Research methods include literature, experimental, and laboratory studies, with phytochemical, characteristic, safety, and organoleptic testing. The results show that DisfaVit has a high bioactive and nutrient content, is safe to consume, and the P3 formula is the most in demand. DisfaVit has the potential to be a neurorehabilitation solution and improve the quality of life of elderly post-stroke patients with dysphagia